MARKET ENTRY TO THE FINNISH ADVENTURE TRAVEL MARKET- CASE STUDY: RAFT-TOUR KARELIA - Beliaeva, Daria (Karelia-ammattikorkeakoulu (Pohjois-Karjalan ammattikorkeakoulu), 2018)
This thesis paper describes the entry strategy into the Finnish adventure travel market for the Raft-tour Karelia company, which wants to expand internationally. The entry mode strategy will be built through the evaluation of the potential market in terms of business environment and competition level in the industry. The business environment analysis includes such factors as political, economic and social-cultural. The entry strategy will include the segmentation, targeting and position of potential cus-tomers. According to the target group identification, relevant marketing tactics will be of-fered to the company as well as the recommendation of the best entry mode. The entry strategy will include a list of potential tourism companies in Finland that Raft-tour Karelia can partner with, website development recommendations and relevant digital marketing activities.